Gendering family policies in post-communist europe : A historical-institutional analysis - Saxonberg, Steven; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
Through the use of a historical-institutional perspective and with particular reference to the Czech Republic, Hungary, Poland and Slovakia; this study explores the state of family policies in Post-Communist Europe. It analyzes how these policies have developed and examines their impact on gender relations for the countries mentioned.
Keywords: Science; Science, general